Trends in Anti-Epileptic Drug Development - Lennart Gram (Behavioural Neurology)
Several avenues are being explored in the development of new anti-epileptic drugs (AEDs). For a number of years efforts have been directed towards compounds which may augment neuronal inhibition, and these efforts have resulted in the development of several valuable drugs. More recently, increased attention has been focused on the role which excitatory transmitters may play in epileptogenesis, and various substances which decrease excitation are currently being investigated at the preclinical level. Since considerable potential still resides in several of the drugs already on the market, resources have been spent on trying to modify/improve the chemical formula of some of these substances, and a number of new drugs has emerged as a result of this approach. The major accomplishments reviewed here in the development of new anti-epileptic drugs suggest that even more successful advances may be achieved in the near future.